A Different View for an Old Disease: NEDDylation and Other Ubiquitin-Like Post-Translational Modifications in Chronic Lymphocytic Leukemia - Arenas, Víctor; Castaño, Jose Luis; Domínguez-García, Juan José; Yáñez, Lucrecia; Pipaón, Carlos (Frontiers in Oncology, 2021)
Despite the enormous amount of molecular data obtained over the years, the molecular etiology of chronic lymphocytic leukemia (CLL) is still nowadays largely unknown. All that information has arisen new therapeutical approaches that have improved life expectancy of the patients but are still not curative. We must increase our knowledge of the molecular alterations leading to the common characteristics of all CLL patients. One of such characteristics is the poor correlation between mRNA and protein expression, that suggests a role of post-translational mechanisms in B-CLL cells. Drugs targeting these processes have indeed demonstrated an effect either alone or in combination with other, aimed at diverse pathways. A recent article unveiled an increment in ubiquitin-like modifications in CLL, with many members of relevant pathways affected. Interestingly, the inhibition of the NEDD8-activating protein NAE reverted a substantial number of those modifications. The present review gets the scarce data published about the role of NEDDylation in CLL together and establishes connections to what is known from other neoplasias, thus suggesting a new sight at the underlying mechanisms in CLL.